Introduction - Harry, C.C.; Vlahakis, G.N. (Women in the History of Philosophy and Sciences, 2023)
Since the last quarter of the twentieth century there has been growing interest in women’s contributions to the histories of science, philosophy, and literature dating back to the very beginnings of these disciplines. This volume offers a contemporary, multinational, multidisciplinary exploration of some of these "hidden figures". © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: dept.phi